Prevalence of Epilepsy and its Association with Exposure to Toxocara canis: A Community Based, Case–control Study from Rural Northern India - Modi, Manish (Ann Indian Acad Neurol, 2018)
OBJECTIVES: Many community-based and hospital-based studies across the world have yielded contradictory results regarding association of positive Toxocara canis serology and epilepsy. The present study was planned to analyze disease burden of epilepsy in rural community of North India and its association with exposure to T. canis in this part of the world. METHODS: A door-to-door screening survey was carried out in the rural community using a validated questionnaire for epilepsy by trained field workers, which was finally confirmed by trained neurologists. The risk factors for epilepsy and for predisposing infections were also enquired. The results were compared with an equal number of age- and sex-matched healthy controls enrolled from the same community. Serologic evaluation was carried out to detect antibodies against T. canis. RESULTS: A total of 41,973 persons from the rural community in 49 villages were enrolled in the study. Two hundred and eleven persons were confirmed to be suffering from active epilepsy, resulting in a crude prevalence of 5 per 1000 population. More than 50% of people with epilepsy were in the second or third decade of life. The prevalence of antibodies to T. canis was similar in people with epilepsy (13.7%; 29 of 211 individuals) and controls (9.95%; 21 of 211 individuals). Of the 151 persons with epilepsy, who underwent CT scan, 34 people (22.3%) had evidence of inflammatory granuloma, thereby confirming high incidence of this infestation in rural Northern India. SIGNIFICANCE: Our study does not support the association between epilepsy and exposure to T. canis in rural Northern Indian population.